Risk factors and clinico-pathological profile of female genital tract malignancies at BPKIHS - Shrestha, Ramesh; Dulal, Soniya; Adhikari, Purbesh; Das, Anamika; Chhetry, Manisha; Shrestha, Sapana; Regmi, Niraj; Basnet, Pritha; Basnet, Tulasha; Thakur, Achala (Nepal Journal of Obstetrics and Gynaecology, 2022)
Aims: To evaluate the risk factors and clinico-pathological profile of patients with female genital tract malignancy. Methods: It was a prospective descriptive study of female genital tract malignancy conducted from December 2019 to December 2020 in the Department of Gynaecology, BPKIHS. Results: Out of 61 cases, cervical cancer was the most common cancer (56.0%) followed by ovarian cancer (21.0%) and gestational trophoblastic neoplasia (13.0%). The mean age of patients was 50.82±12.81 years. 38 (62.3%) were postmenopausal; 59 (96.7%) had good performance status at presentation (ECOG 1 and 2); 41 (67.2%) had early stage disease (stage I and II). 36 (59.0%) were referred outside for further treatment and majority belonged to cervical cancer (n=29;80.5%) for radiotherapy services. Eight (13.1%) patients had disease recurrence and one patient (1.6%) had death during the study duration. Among patients with cervical cancer, the mean age at marriage and at first pregnancy were 17.24±2.32 years and 19.47±2.51 years respectively. Majority of them had poor local hygiene (n=27; 79.4%). The most common presentation was post menopausal bleeding (n=29; 85.3%) and most common histology was squamous cell carcinoma (n=30; 88.3%). Conclusions: Cervical cancer is the most common female genital tract cancer followed by ovarian and gestational trophoblastic tumor.Keywords: clinico-pathological, female, genital tract, malignancy, risk factors.